Sustainable Diets Brief: Produce prescription programs: An innovative strategy for improving healthy food access - Shostak, Sara; Black, Jolie; Daley, Stacey (Journal of Agriculture, Food Systems, and Community Development, 2026)
First paragraph: How Do Produce Prescription Programs Work? Produce prescription programs (PPPs) are an innovative strategy for improving healthy food access in order to prevent or treat diet-related illness. Healthcare providers identify patients based on factors such as food insecurity, income, and diet-related health conditions, and then provide “prescriptions” for healthy food, such as vouchers, tokens, or coupons for free or subsidized fresh produce that can be used at grocery stores, farmers markets, or local farms. Many programs also provide nutrition education, recipes, and guidance on food preparation and storage. . . .